2006
DOI: 10.1111/j.1365-4632.2006.02865.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum eosinophil cationic protein in children with atopic dermatitis

Abstract: Background: Eosinophil cationic protein (ECP) is a cytotoxic agent secreted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…falciparum coinfection among males than females since ECP levels were highest among the coinfected group. The observed positive correlation between relative eosinophil count and ECP level agrees with previous studies [22, 23], while others [20] found no such association. Immune responses to hookworm larvae involve a series of cellular and molecular interactions with immunoglobulin E-activated mast cells [24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…falciparum coinfection among males than females since ECP levels were highest among the coinfected group. The observed positive correlation between relative eosinophil count and ECP level agrees with previous studies [22, 23], while others [20] found no such association. Immune responses to hookworm larvae involve a series of cellular and molecular interactions with immunoglobulin E-activated mast cells [24].…”
Section: Discussionsupporting
confidence: 92%
“…falciparum alone and those with no infections. However, other parasitic infections as well as allergies have been associated with elevated plasma ECP levels [21–23] and should be accounted for in studies investigating its association with any specific infection.…”
Section: Discussionmentioning
confidence: 99%
“…parasitic infection, certain cancers and autoimmune diseases). 28, 30, 31 Increases in tissue mast cells and peripheral eosinophil counts have also been evaluated, but with similar inconsistent association. 30, 3234 …”
Section: Biomarkersmentioning
confidence: 99%
“…Correlation between serum IgE levels and AD severity has been suggested, but study results are partly conflicting ( 10 , 11 ). A recent study combining panimmunoglobulin IA for 2–4 days with subsequent biweekly omalizumab treatment for 6 months showed that after initial reduction in total serum IgE levels by IA, free IgE levels continued to fall during omalizumab administration and began to increase again during treatment-free follow-up.…”
Section: Discussionmentioning
confidence: 99%